Classification and morphology of middle mesial canals of mandibular first molars in a southern Chinese subpopulation: a cone-beam computed tomographic study - Yang, Yeqing (BMC Oral Health, 2020)
BACKGROUND: Cone-beam computed tomography (CBCT) was employed to study the morphology and curvature of middle mesial canals (MMCs) of mandibular first molars (MFMs). METHODS: CBCT scanning was performed on MFMs of 1100 patients. Patients' images that met the inclusion criteria were divided into group A (< 40 years old) and group B (≥ 40 years old) for further study. The images were used to study the incidence of MMCs at different ages, measure the curvature of MMCs in the mesiodistal and buccolingual directions using the Schneider method, and observe the anatomical morphology of the mesial root canal system. All statistical analyses were performed by using SPSS 21.0 software. Quantitative data were presented as mean ± standard deviation. Student’s t-test was used to calculate the statistical significance. P < 0.05 was considered statistically significant. RESULTS: In 875 patients, 1750 MFM images met the inclusion criteria. Among these cases, 158 MFMs contained an MMC, yielding an incidence rate of 9.03%. The incidence rate of MMCs was 11.22% in group A and 6.61% in group B, and this difference was statistically significant (P < 0.05). The curvature in the mesiodistal direction was 29.39 ± 8.53° in group A and 26.06 ± 8.50° in group B, and this difference was also significant (P < 0.05). The curved regions in groups A and B were often located in the middle 1/3 of canal. No significant difference in the distance between MMC orifices and mesiobuccal canal orifices or mesiolingual canal orifices was noted (P > 0.05). The most common mesial root canal morphological type was type II (3-2) (53.80%). CONCLUSION: The incidence of MMCs in MFMs declined as age increased. The canal systems of MMCs were varied and complex, mainly exhibiting an obvious mesiodistal curve. CBCT is an outstanding method to help guide root canal therapy. *Yeqing Yang and Buling Wu have contribute equally to this article.